Siklus Tata Kelola Organisasi Badan Pemusyawaratan di Desa Sepakat, Kabupaten Kutai Kartanegara - Juliansyah Roy; Selly Swandari (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The Law on Villages has shifted the position of the Village Consultative Body (BPD) as an element of village administration to become a village institution. As a village institution, the function and position of the BPD include the village legislature. This regulation also demands changes in organizational governance for BPD, particularly in Sepakat Village (Loa Kulu District, Kutai Kartanegara Regency). This encourages researchers to look at and provide recommendations related to the organizational governance of BPD in Sepakat. The approach used in this service is a qualitative-based descriptive analysis. The process here focuses on four elements. In the first topic of discussion is the organizational structure of the BPD in Sepakat Village, the second is the division of the main tasks and functions of each BPD member, the third includes the standard operating procedure (SOP) for implementing activities and the fourth is the supervision of the BPD. Through data collection with in-depth interviews, it designed the analysis model with five units (checking the data got, reducing data, applying data, namely data processing, analyzing, and drawing conclusions). to get an overview of the field. Practical ideas suggest that there should be regular supervision and training of human resources for BPD of Sepakat Village